(untitled) (Research, Society and Development, 2023)
Objective: to quantify the prevalence of Spirituality and Religiosity (SR) as an important factor in the course of treatment of patients diagnosed with dyspepsia. Methods: This was a cross-sectional observational study of quantitative approach, descriptive in nature, by statistical analysis of questionnaires, which were applied to patients diagnosed with dyspepsia and seen in a gastroenterology clinic in the city of Cascavel, Paraná. Results: 100 patients were selected, 100% diagnosed with dyspepsia, and 68% reported that in moments of difficulty, anxiety, nervousness or stress the symptoms of abdominal discomfort (pain, burning sensation and early satiety) worsen significantly. Of these, when asked which tools of E/R help them in these moments, the following results were obtained: 73% get improvement with prayer, 36.8% with meditation, 21% with reading, and 21% by attending religious services. Finally, 57% reported that in moments of mental, emotional, and spiritual stability there is a significant improvement in the symptoms of abdominal discomfort. Final considerations: It was evident that most dyspeptic patients understand Spirituality and Religiosity (SR) as a relevant and functional factor in their therapy. Because it constitutes a fundamental issue of integral care, it is of utmost importance that these tools be incorporated with more emphasis in the care of these patients.